Antibacterial and Antimycotic Activity of Epilobium angustifolium L. Extracts: A Review - Mariola Dreger; Artur Adamczak; Joanna Foksowicz-Flaczyk (MDPI AG, 2023)
The aim of this work was to provide an overview of available information on the antibacterial and antifungal properties of Epilobium angustifolium extracts. A literature search of Scopus, PubMed/Medline, and Google Scholar for peer-reviewed articles published between January 2000 and June 2023 was undertaken. A total of 23 studies were eligible for inclusion in this review. Significant variation of antimicrobial activity depending on the tested species and strains, type of extract solvent, or plant organs utilized for the extract preparation was found. E. angustifolium extracts were active against both Gram-positive and Gram-negative bacteria and showed antimycotic effects against the fungi of Microsporum canis and Trichophyton tonsurans and the dermatophytes Arthroderma spp. Greater susceptibility of Gram-positive than Gram-negative bacteria to fireweed extracts was found. A strong antibacterial effect was recorded for Staphylococcus aureus, Bacillus cereus, Micrococcus luteus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii including multi-drug resistant strains. E. angustifolium extract might find practical application as an antimicrobial in wound healing, components of cosmetic products for human and animals, or as food preservatives.